2012
DOI: 10.1177/1756283x12446158
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in patients with inflammatory bowel disease: insights for the clinician

Abstract: Abdominal pain is a common symptom in patients with inflammatory bowel disease (IBD) and has a profound negative impact on patients' lives. There are growing data suggesting that pain is variably related to the degree of active inflammation. Given the multifactorial etiologies underlying the pain, the treatment of abdominal pain in the IBD population is best accomplished by individualized plans. This review covers four clinically relevant categories of abdominal pain in patients with IBD, namely, inflammation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 138 publications
(210 reference statements)
1
60
0
5
Order By: Relevance
“…The clinical presentation of UC patients in this study was similar to other studies were bloody diarrhea and abdominal pain are the most common presentations [2,9,11,14,16,17]. For instance, Al-Qabandi, et al [14] reported bloody diarrhea in 94% and abdominal pain in 78% of UC patients.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The clinical presentation of UC patients in this study was similar to other studies were bloody diarrhea and abdominal pain are the most common presentations [2,9,11,14,16,17]. For instance, Al-Qabandi, et al [14] reported bloody diarrhea in 94% and abdominal pain in 78% of UC patients.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, Al-Qabandi, et al [14] reported bloody diarrhea in 94% and abdominal pain in 78% of UC patients. The abdominal pains are attributed to intestinal distension secondary to the disease itself, to fibrotic stricture, adhesions or following surgical interventions [17]. Thirty-eight per cent of UC patient in this study had history of weight loss at presentation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The major symptom of IBD is abdominal pain, which is described as a cramping sensation, varying in intensity and with exacerbations (Srinath et al, 2012). There are two types of abdominal pain: somatic, which is musculoskeletal; and visceral, caused by stretching of the viscera by obstruction or widely affected inflammation.…”
Section: Discussionmentioning
confidence: 99%